Breaking the Barriers: Women's Participation in the First Election in Indonesia, 1955 - Ningrum, Siti Utami Dewi; Mukhtar, Mutia Kamalia; Tri Wulandari, Nisa A'rafiyah (History Department, Semarang State University and Historian Society of Indonesia, 2024)
Women are often absent from the political sphere which is considered the domain of men. Indonesia's first general election held in 1955 became an important political event. The democratic party not only shows the political attitude of the Indonesian government as a newly independent country, but also the participation of the people in it, including women. This study seeks to trace the breakthroughs made by women in the first election in Indonesia. Historical research methods are used in this research, utilizing primary and secondary sources in the form of archives, newspapers, photographs, and relevant literary sources. The results of the study show that women are able to break down the barriers of gender construction to be active in elections with various roles they have. Various efforts were also made to increase women's participation in the first general election, such as the establishment of various regulations and laws, education, courses, and political socialization for women, as well as the support of various facilities provided to support women's involvement in elections.